2019
DOI: 10.3847/2041-8213/ab2da5
|View full text |Cite|
|
Sign up to set email alerts
|

WFIRST and EUCLID: Enabling the Microlensing Parallax Measurement from Space

Abstract: The Wide Field Infrared Survey Telescope (WFIRST) is expected to detect hundreds of free-floating planets, but it will not be able to measure their masses. However, simultaneous microlensing observations by both Euclid and WFIRST spacecraft, separated by ∼100, 000 km in orbits around the Sun-Earth L2 Lagrange point, will enable measurements of microlensing parallax for low-mass lenses such as free-floating planets. Using simple Fisher matrix estimates of the parallax measurement uncertainties, we show that hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The stellar mass range can also be probed by lensing of Type-Ia supernovae [46]. Using parallax measurements in lensing can probe asteroid to planet masses [47,48]. Should numerous microlensing events be detected, the data on lightcurves may help us estimate the subhalo mass function and perform dark matter astrometry, in particular help identify departures from the Standard Halo Model such as the presence of tidal streams, as already constrained by weak lensing in the time domain [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The stellar mass range can also be probed by lensing of Type-Ia supernovae [46]. Using parallax measurements in lensing can probe asteroid to planet masses [47,48]. Should numerous microlensing events be detected, the data on lightcurves may help us estimate the subhalo mass function and perform dark matter astrometry, in particular help identify departures from the Standard Halo Model such as the presence of tidal streams, as already constrained by weak lensing in the time domain [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…While the exact orbital elements are not known yet, it is safe to assume that the orbits will be comparable to the current orbit of the Gaia telescope, with an orbital radius R ∼ 300, 000 km and a period of ∼ 180 days. Using these parameters, Bachelet & Penny (2019) have shown that simultaneous observations from the two telescopes unlock the parallax measurement down to the FFP regime, if the telescope's separation is at least ≥ 100, 000 km. We use these parameters for the rest of this work.…”
Section: Orbital Elementsmentioning
confidence: 99%
“…Recently, it has been demonstrated that the Roman observations from the Earth-Sun L2 point will be sufficient to detect parallax for microlensing events with t E 5 days, due to the orbit of the L2 point around the Sun (Bachelet & Penny 2019). This will ensure strong constraints on the mass and distance of the ∼ 1, 500 bound planets expected to be detected by Roman (Penny et al 2019).…”
Section: Mass-distance Relations From Lens-source Relative Proper Motionmentioning
confidence: 99%
See 2 more Smart Citations